Design, delivery and effectiveness of health practitioner regulation systems: an integrative review - Kathleen Leslie; Ivy Lynn Bourgeault; Anne-Louise Carlton; Madhan Balasubramanian; Raha Mirshahi; Stephanie D. Short; Jenny Carè; Giorgio Cometto; Vivian Lin (BMC, 2023)
Abstract Background Health practitioner regulation (HPR) systems are increasingly recognized as playing an important role in supporting health workforce availability, accessibility, quality, and sustainability, while promoting patient safety. This review aimed to identify evidence on the design, delivery and effectiveness of HPR to inform policy decisions. Methods We conducted an integrative analysis of literature published between 2010 and 2021. Fourteen databases were systematically searched, with data extracted and synthesized based on a modified Donabedian framework. Findings This large-scale review synthesized evidence from a range of academic (n = 410) and grey literature (n = 426) relevant to HPR. We identified key themes and findings for a series of HPR topics organized according to our structures-processes-outcomes conceptual framework. Governance reforms in HPR are shifting towards multi-profession regulators, enhanced accountability, and risk-based approaches; however, comparisons between HPR models were complicated by a lack of a standardized HPR typology. HPR can support government workforce strategies, despite persisting challenges in cross-border recognition of qualifications and portability of registration. Scope of practice reform adapted to modern health systems can improve access and quality. Alternatives to statutory registration for lower-risk health occupations can improve services and protect the public, while standardized evaluation frameworks can aid regulatory strengthening. Knowledge gaps remain around the outcomes and effectiveness of HPR processes, including continuing professional development models, national licensing examinations, accreditation of health practitioner education programs, mandatory reporting obligations, remediation programs, and statutory registration of traditional and complementary medicine practitioners. Conclusion We identified key themes, issues, and evidence gaps valuable for governments, regulators, and health system leaders. We also identified evidence base limitations that warrant caution when interpreting and generalizing the results across jurisdictions and professions. Themes and findings reflect interests and concerns in high-income Anglophone countries where most literature originated. Most studies were descriptive, resulting in a low certainty of evidence. To inform regulatory design and reform, research funders and governments should prioritize evidence on regulatory outcomes, including innovative approaches we identified in our review. Additionally, a systematic approach is needed to track and evaluate the impact of regulatory interventions and innovations on achieving health workforce and health systems goals.